“On Wooden Churches”: William Scott and the Colonial Church - Turner, Emily (2014)
The use of wood in Gothic Revival buildings was a contentious issue in the middle of the nineteenth century. Because of the need in the British colonies to use timber in church construction due to financial and material restraints, a re-examination of wood as a building medium consistent with the principles of the Revival became necessary. For the Cambridge Camden Society, the breakthrough in understanding timber as a truly ecclesiological material came in an essay by Rev. William Scott entitled “On Wooden Churches” (1848), which traced the historical and symbolic features of wood in ecclesiastical design. This article examines the rationale that Scott put forward to validate the use of the medium in colonial settings, focusing on his theological and historical arguments as well as his scheme for practical application of theoretical constructs. This study will also demonstrate the way in which Scott’s advice was applied in the colonial setting in the case study of Frederick Thatcher’s Old St. Paul’s, Wellington in New Zealand.
Keywords: Gothic Revival -- Ecclesiology -- William Scott -- Church Architecture -- Frederick Thatcher